Two-phase flow of air and soybeans during a silo discharge process - Chuayjan, W.; Jumpen, W.; Boonkrong, P.; Wiwatanapataphee, Benchawan (2012)
The paper aims to present mathematical model and numerical simulation of a granular material flow during a silo discharge process. The material flow in the silo is a form of two-phase flow consisting of particulates and an interstitial fluid. These two phases are soybeans and air. The homogeneous flow is assumed. The effect of the bottom design of the silo on the two-phase flow is investigated. The bottom shape including flat shape and cone shape and the diameter of outlet width including 0.08 m and 0.12 m are chosen for this investigation. The results show that the mathematical model can capture the granular material flow in the silo. The bottom design has significant effect on the velocity, pressure and shear rate in the granular material during the silo discharge process.